Variasi Basis Salep Minyak Kemiri (Aleurites moluccana) dan Uji Daya Penyembuhannya Pada Luka Kelinci - Paulina Veronika Yamlean; Edwin De Queljoe; Widdhi Bodhi (Fakultas Farmasi Universitas Pancasila, 2019)
Candlenut plant in Indonesia is still limited to traditional uses such as cooking spices and traditional medicines. Only a few research has been done on Candlenut oil. The purpose of this study is to make ointment base variations toward the quality of Candlenutoil ointment with 12.5% concentration andits healing potential teston open wounds in rabbits infected with the Staphylococcus aureus bacteria. This research method is a laboratory experiment using 3 variations of base ointment namely hydrocarbon base, absorption base and water soluble base with Candlenut oil test solution of 12.5%. The results showed the quality test of the ointment with three variations of ointment base fulfilled the requirements of organoleptic test, homogeneity test, and pH test, but Candlenutoil ointment of 12.5% with hydrocarbon base did not meet the scattering power requirement. The results of the ANOVA test showed no significant difference between the base variations of the ointment and the size of wound healing. This shows that the three variations of the 12.5% Candlenut oil ointment base can be used in healing open wounds on rabbits (Oryctolagus cuniculus) infected with the Staphylococcus aureus bacteria.